NILAI MORAL DALAM TRADISI SANTRI PADA NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY (KAJIAN SOSIOLOGI SASTRA) - Ahmad Ilzamul Hikam; Komariah Bonawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to describe illustrations of moral values applied by santri in the novel Bidadari Bermata Berahan by Habiburrahman El Shirazy. In analyzing a literary work, we need an approach as a starting point in its study. One approach used to study this literary work is literary sociology. The reason researchers use a literary sociology approach is because we often apply moral values in dealing with society. Literary sociology is an approach that studies, understands and evaluates literary works from a social or societal perspective.